Psychopathic traits and offender characteristics amongst female offenders in a South African correctional centre - Basson, Sasha (University of the Free State, 2014)
Psychopathy among female offenders remains a relatively unexplored area despite an increase in offending behaviour amongst females. This study investigates psychopathy and the demographic variables among a sample of female offenders. A non-experimental research method with a criterion group design was implemented. The participants consisted of 100 female offenders currently sentenced at the Kroonstad Correctional Centre in the Free State. The data was collected through the use of two questionnaires, the Psychopathic Personality Inventory-Revised (PPI-R) (Lilienfeld & Andrews, 1996) and a self-compiled demographic risk questionnaire developed from the Level of Service Inventory-Revised: Short Version (LSI-R: SV) (Andrews & Bonta, 1995). Descriptive statistics were calculated to determine the prevalence of psychopathy among the sample and a multivariate analysis was used to investigate any significant difference in mean psychopathy scores. Finally effect size (d) was calculated to determine whether any practical significance for the results exists. Results indicated that 90% of the sample in each age group complied with the cut-off score of the PPI-R, which is indicative of psychopathy. The differences in the average PPI-R score indicated a significant result at the 1% level for one demographic variable, namely primary caregiver. This indicates that the findings are of average practical significance. A one-way analysis of variance found a significant difference on the 1% level for blame externalization. This indicates a large effect size, which shows that the result is of practical importance. Thus it seems that female offenders presenting with psychopathy, who were raised by one parent or their grandparents show higher tendencies to blame their problems on others.

Psigopatie onder vroulike oortredes bly ‘n relatiewe onbekende gebied ten spyte van ‘n toename in misdadige gedrag onder vroue. Hierdie studie ondersoek psigopatie en die demografiese veranderlikes onder 'n steekproef van vroulike oortreders. 'n Nie-eksperimentele navorsing metode met 'n maatstaf groep ontwerp is geïmplementeer. Die deelnemers het bestaan uit 100 vroulike oortreders tans gevonnis by die Kroonstad Korrektiewe Sentrum in die Vrystaat. Die data is ingesamel deur middel van twee vraelyste, die Psychopathic Personality Inventory - Revised (PPI-R) (Lilienfeld & Andrews, 1996) en 'n self-saamgestel demografiese risiko vraelys ontwikkel uit die Level of Service Inventory-Revised: Short Version (LSI - R SV) (Andrews & Bonta, 1995). Beskrywende statistiek was bereken om die voorkoms van psigopatie onder die steekproef vas te stel en n’ meerveranderlike analise is gebruik om 'n beduidende verskil in die gemiddelde psigopatie tellings te ondersoek. Ten slotte is effekgrootte (d) bereken om te bepaal of daar enige praktiese betekenis vir die resultate bestaan. Resultate het aangedui dat 90% van die steekproef in elke ouderdomsgroep voldoen aan die afsnypunt van die PPI-R, wat 'n aanduiding van psigopatie is. Die verskille in die gemiddelde PPI-R telling het betekenis gedui op die 1% vlak vir een demografiese veranderlike, naamlik primêre versorger. Dit dui daarop dat die bevindinge van gemiddelde paraktiese betekenis is. ‘n Eenrigting-variansieanalise het 'n beduidende verskil op die 1%-vlak vir skuld eksternalisering aangedui. Dit dui op ‘n groot effek grootte, wat toon dat die resultaat van praktiese belang is. So blyk dit dat vroulike oortreders wat psigopatie toon wat deur een van hulle ouers of hul ouma en oupa groot gemaak is wys hoër tendense om hul probleme te blameer op die ander.
Keywords: Psychopathic Personality Inventory-Revised (PPI-R); Correctional centre; Female offenders; Psychopathy; Demographic variables; Woman prisoners; Female offenders South Africa; Thesis (M.A. (Psychology)) - University of the Orange Free State, 2014